Inertial Sensor Self-Calibration Module Using Attitude Heading And Reference System For Autonomous Underwater Vehicle Navigation - Abd Kadir, Abdul Aziz; Abdul Kadir, Herdawatie (IIUM Engineering Journal, 2026)
This research addresses the complex task of enhancing navigation accuracy in Autonomous Underwater Vehicles (AUVs), a self-propelled robotic system used for ocean exploration, environmental monitoring, and underwater interventions. A core component of AUV navigation is an Inertial Measurement Unit (IMU), a sensor suite that tracks orientation and motion by measuring accelerations and angular rates. However, the IMU is highly susceptible to noise interference, which degrades accuracy and reliability. To address these challenges, this study introduces an innovative Inertial Sensor Self-Calibration Module that dynamically adjusts calibration parameters in real time, thereby compensating for sensor drift and inaccuracies. The research further conducts a comparative analysis of several calibration and filtering techniques integrated into the AUV's Inertial Navigation System (INS), including Magnetic Calibration, the Extended Kalman Filter (EKF), the EKF with Measurement Noise, the EKF with Process Noise, and the Attitude and Heading Reference System (AHRS) Filter. Among these, the AHRS filter demonstrated superior precision, achieving the lowest average error of 1.06 degrees with a standard deviation of 0.345 degrees in angle measurements, an improvement of up to 97.81% compared to raw data. These findings highlight the effectiveness of the AHRS filter in improving navigation accuracy in complex underwater environments. The insights gained from this research not only deepen the understanding of noise impact and sensor calibration in AUV systems but also pave the way for future innovations in oceanic exploration, environmental monitoring, and underwater interventions. ABSTRAK: Kajian ini adalah berkenaan menangani tugas kompleks meningkatkan ketepatan navigasi Kenderaan Bawah Air Autonomi (AUV), iaitu sistem robotik berkuasa sendiri digunakan bagi penerokaan lautan, pemantauan alam sekitar, dan intervensi bawah air. Komponen utama navigasi AUV bergantung pada Unit Pengukuran Inersia (IMU), iaitu rangkaian pengesan orientasi dan pergerakan dengan mengukur pecutan dan kadar sudut. Namun, IMU sangat terdedah kepada gangguan bunyi, di mana ianya mengurangkan ketepatan dan kebolehpercayaan. Oleh itu, kajian ini memperkenalkan Modul Kalibrasi Diri Pengesan Inersia yang inovatif, iaitu secara dinamik menyesuaikan parameter kalibrasi pada masa nyata, secara efektif mengimbangi hanyutan sensor dan ketidaktepatan. Kajian ini juga membuat analisis perbandingan beberapa teknik kalibrasi dan penapisan yang diintegrasikan pada Sistem Navigasi Inersia (INS) AUV, termasuk Kalibrasi Magnetik, Penapis Kalman Lanjutan (EKF), EKF dengan Bunyi Pengukuran, EKF dengan Bunyi Proses, dan Penapis Sistem Rujukan Sikap dan Haluan (AHRS). Antara teknik-teknik ini, penapis AHRS menunjukkan ketepatan terbaik, dengan ralat purata terendah iaitu 1.06 darjah dan sisihan piawai pengukuran sudut 0.345 darjah dan peningkatan sehingga 97.81% berbanding data mentah. Penemuan ini menunjukkan keberkesanan penapis AHRS dalam meningkatkan ketepatan navigasi pada persekitaran bawah air yang kompleks. Dapatan kajian ini bukan sahaja memperdalam pemahaman tentang kesan bunyi dan kalibrasi pengesan dalam sistem AUV, tetapi turut membuka ruang terhadap inovasi masa depan dalam penerokaan lautan, pemantauan alam sekitar, dan intervensi bawah air.